The influence of sex steroid hormones in the immunopathology of experimental pulmonary tuberculosis - Bini, Estela Isabel (2014)
The relation between men and women suffering pulmonary tuberculosis is 7/3 in favor to males. Sex hormones could be a significant factor for this difference, considering that testosterone impairs macrophage activation and pro-inflammatory cytokines production, while estrogens are proinflammatory mediator's inducer. The aim of this work was to compare the evolution of tuberculosis in male and female mice using a model of progressive disease. BALB/c mice, male and female were randomized into two groups: castrated or sham-operated, and infected by the intratracheal route with a high dose of Mycobacterium tuberculosis strain H37Rv. Mice were euthanized at different time points and in their lungs were determined bacilli loads, inflammation, cytokines expression, survival and testosterone levels in serum. Non-castrated male mice showed significant higher mortality and bacilli burdens during late disease than female and castrated male animals. Compared to males, females and castrated males exhibited significant higher inflammation in all lung compartments, earlier formation of granulomas and pneumonia, while between castrated and non-castrated females there were not significant differences. Females and castrated males expressed significant higher TNF-α, IFN γ, IL12, iNOS and IL17 than non-castrated males during the first month of infection. Serum Testosterone of males showed higher concentration during late infection. Orchidectomy at day 60 post-infection produced a significant decrease of bacilli burdens in coexistence with higher expression of TNFα, IL-12 and IFNγ. Thus, male mice are more susceptible to tuberculosis than females and this was prevented by castration suggesting that testosterone could be a tuberculosis susceptibility factor.